The global urban agenda and its relevance in Russia - Kozmin, Alexei (project baikal, 2026)
The article explores traditional local building materials and construction techniques as tools for adapting architecture and cities to climate change. The study is inspired by the 2025 Venice Architecture Biennale curated by Carlo Ratti, where wood and bio-based materials are presented as carriers of “natural intelligence” and a foundation for regenerative architecture. Special attention is given to master plans as a key instrument of climateresponsive urban development. The article reviews selected Biennale projects and examines the potential of contemporary timber construction in Siberia, considering clim